Cot-side electroencephalography for outcome prediction in preterm infants: observational study. Issue 2 (24th September 2010) - West, Claire R; Harding, Jane E; Williams, Chris E; Nolan, Melinda; Battin, Malcolm R
Abstract : Objective: To assess the use of two-channel electroencephalographical (EEG) recordings for predicting adverse neurodevelopmental outcome (death or Bayley II mental developmental index/psychomotor developmental index < 70) in extremely preterm infants and to determine the relationship between quantitative continuity measures and a specialist neurophysiologist assessment of the same EEG segment for predicting outcome. Design: Observational study. Setting: The study was conducted in a neonatal intensive care unit. Patients: Preterm infants born <29 weeks' gestation. Interventions: Two-channel EEGs using the reBRM2 monitor (BrainZ Instruments, Auckland, New Zealand) within 48 h of delivery. One-hour segments were analysed, blinded to the clinical outcome, by off-line quantitative analysis of continuity and a review of the raw EEG by a neurophysiologist. Main outcome measures: Developmental assessment at a median of 15 months' corrected age. Results: 76 infants had an EEG within 48 h of delivery and a developmental assessment. The analysed segment of the EEG was obtained at 24 (3–48) h of age (median (range)). The neurophysiologist's assessment was a better predictor of adverse outcome than the continuity measures (positive predictive value 95% CI 75 (54% to 96%) vs 41 (22% to 60) at 25-µV threshold, negative predictive value 88 (80% to 96%) vs 84 (74% to 94%) and positive likelihood ratio 9.0 (3.2 to 24.6) vs 2.0 (1.2 to 3.6)). All the infants with definite seizures identified by the neurophysiologist had poor outcomes. Conclusions: Modified cot-side EEG has potential to assist with identification of extremely preterm infants at risk for adverse neurodevelopmental outcomes. However, analysis by a neurophysiologist performed better than the currently available continuity analyses.